Validity and Motivation of Decisions in Criminal Proceedings - ABZALBEKOVA, Maral; ARENOVA, Leila; ZBINSKAYA, Yevgeniya; SULTANBEKOVA, Gulmira; YESSENTAEVA, Nazym (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018, 2019)
The article examines the concept and meaning of the substantiation and motivation of decisions in criminal proceedings. Achievement of the objectives of the criminal process is directly dependent on the soundness and motivation of criminal proceedings. The requirement that the decision was not only justified, but also motivated, follows from the fact that motivation increases the soundness of the decision, gives it internal and external persuasiveness, simplifies the process of the decision taken by the participants. Motivation is considered a type of reasonableness, where the speculator recognizes the indication of the reason for choosing the option of action. The goal of the article is the absolute theoretical-legal analysis of the validity and motivation of criminal procedural decisions, the introduction of guarantees for the improvement of criminal procedural law and its use.